An Exploratory Study on Opinion of Tracking System For Patient With Dementia among Mental Health Team Member of Pune City - Pravesh Shukla1 , Sheela Upendra2 , Sharadha Ramesh3 (Indian Journal of Forensic Medicine & Toxicology, 2020)
Introduction and objective: Patient with dementia who wander are at high risk of harm self and posethreat to self and stress and worry for care givers too. Care givers feel under stress and worry dueto this symptoms. The objective of this study was to to determine the opinion from mental health careteam member or tracking system for patient with Dementia and to find association between opinions ofmental health team members and selected demographic variable. Material and Method: Quantitative NonExperimental research approach was used and research design was Descriptive Exploratory Research Designto explore on opinion of tracking system for patient with dementia among mental health team member ofPune city. Sample size was 30 and non-probability convenience sampling technique. Tool had two sections.Part A involved the demographic variables age, gender, marital status, designation, and years of experienceand part B was structured opinionnair 0 to 2 numerical rating scale which is further divided into 3 categoriesYes, No, Don’t Know. Result: Mental health team members is in opine for demand of tracking system forpatient with dementia. ANOVA test used to check the association between opinion of mental health teammember and selected demographic variable. The p-values are less than 0.05, there is a significant associationbetween opinion of mental health team member and years of experience of mental health team members andwith other demographic variables there is no any significant association.